Medical students' subjective ratings of stress levels and awareness of student support services about mental health. Issue 1052 (6th March 2013) - Walter, Garry; Soh, Nerissa Li-Wey; Norgren Jaconelli, Sanna; Lampe, Lisa; Malhi, Gin S; Hunt, Glenn
Abstract : Purpose: To descriptively assess medical students' concerns for their mental and emotional state, perceived need to conceal mental problems, perceived level of support at university, knowledge and use of student support services, and experience of stresses of daily life. Study design: From March to September 2011, medical students at an Australian university were invited to complete an anonymous online survey. Results: 475 responses were received. Students rated study and examinations (48.9%), financial concerns (38.1%), isolation (19.4%) and relationship concerns (19.2%) as very or extremely stressful issues. Knowledge of available support services was high, with 90.8% indicating they were aware of the university's medical centre. Treatment rates were modest (31.7%). Students' concerns about their mental state were generally low, but one in five strongly felt they needed to conceal their emotional problems. Conclusions: Despite widespread awareness of appropriate support services, a large proportion of students felt they needed to conceal mental and emotional problems. Overall treatment rates for students who were greatly concerned about their mental and emotional state appeared modest, and, although comparable with those of similarly aged community populations, may reflect undertreatment. It would be appropriate for universities to address stressors identified by students. Strategies for encouraging distressed students to obtain appropriate assessment and treatment should also be explored. Those students who do seek healthcare are most likely to see a primary care physician, suggesting an important screening role for these health professionals.